Cynicism and the Collapse of Multilateralism - Mahbi Maulaya (AEGIS : Journal of International Relations, 2020)
International order is now witnessing the declining efficacy and extremely fragile condition of multilateralism. Several states start to doubt and leave international treaties, agreements, organizations, and institutions. This circumstance led into the speculation of “Multilateralism Collapse". Yet, there is only a small number of International Relations scholars who attempt to detect the general pattern that indicate the fundamental reason of relevant states to withdraw from multilateralism manifestation. Hence, this study is a preliminary attempt to fill the gap by providing a concrete explanation on the reason why the multilateralism is failing. This paper argues that the growing cynicism among the relation of international actors is served to be the reason of multilateralism free fall. There are two types of cynicism which this paper has discovered, the cynicism as a trigger and cynicism as a statement. Cynicism as a trigger tracked whereby the relevant state’s withdrawal from the multilateralism manifestation is merely caused by a sense of distrust. On the other hand, cynicism as a statement is the expression of relevant states to justify its withdrawal action and distract world’s attention from its hidden interest. Since this study requires a specific and deep interpretation on sets of event and data, the utilization of qualitative method was considered effective. This study applied two theoretical frameworks, namely cynicism and multilateralism.